THE EFFECT OF COMMUNICATION AND MOTIVATION TO WORK ACHIEVEMENT WITH COMPETENCE AS INTERVENING VARIABLES IN NURSE IN BHAYANGKARA HOSPITAL PALEMBANG - Hanafi, Agustina; Soebyakto, Bambang Bemby; Saputra, Ade Candra (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study focuses on the influence of communication and motivation on work performance with competence as an intervening variable. Hypothesis tested in this research are: (1) There are significant positive influence from communication and motivation variable to competence (2) There is significant positive influence from communication variable, motivation and competence to work performance. The sample used in this research is 110 respondents to nurses at Bhayangkara Hospital Palembang. The data used were obtained from the results of the research on nurses at Bhayangkara Hospital Palembang and analyzed using Structural Equation Model with the help of Structural Linear Relations program. Test results show that, (1) Communication has a positive effect on Competence. Motivation has a negative effect on Competence. (2) communication, motivation and competence variables have a positive effect on work performance on nurses at Bhayangkara Hospital Palembang. This research is expected to be useful, among others, for Nurses Bhayangkara Hospital Palembang as consideration in decision making for hospital progress. Bhayangkara Palembang, and for further research this research can be one reference for research related to communication, motivation, competence and work performance.